2004
DOI: 10.1093/ndt/gfh406
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with access blood flow in native vessel arteriovenous fistulae

Abstract: Our findings suggest that a single Qa threshold for angiography in all patients may be simplistic, and that the optimal threshold might vary by patient subgroup. The strong association between SBP and Qa suggests that adjusting Qa for SBP may improve the specificity of access screening. Further work is required to determine whether such modifications to current practice would improve the predictive power of Qa measurements for detection of stenosis in AVF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 18 publications
3
15
2
Order By: Relevance
“…These parameters were not recorded in the present study. Despite this omission, we can confirm that the found factors are related to decreased Qa [50] . To what extent demographics and cardiovascular risk factors are specifically related to decreased Qa remains to be investigated in a study including both CO and blood pressure.…”
Section: Limitationssupporting
confidence: 51%
“…These parameters were not recorded in the present study. Despite this omission, we can confirm that the found factors are related to decreased Qa [50] . To what extent demographics and cardiovascular risk factors are specifically related to decreased Qa remains to be investigated in a study including both CO and blood pressure.…”
Section: Limitationssupporting
confidence: 51%
“…This study confirms the clinical observation that MAP has a large effect on Q and underscores the importance of avoiding hypotension in preventing thrombosis. It often has been proposed that Q should be normalized for MAP (Q/MAP) or systolic pressure so as to offset the effect of hemodynamic changes on Q (31)(32)(33). This adjustment assumes that a change in MAP causes a proportionally equal change in Q.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown, however, that the site of stenosis varies according to the type of AVF, the most common location being the juxta-anastomotic region in the case of forearm radiocephalic AVFs, and the outflow region for upper-arm brachiocephalic and brachiobasilic AVFs (2)(3)(4)(5). It has also been reported that the access blood flow rate (Qa), a measurement widely accepted as a means for detecting access dysfunction, also varies according to the site of the AVF, being lower in the more distal accesses than in the more proximal accesses (6,7). Some researchers have found that the Qa threshold indicative of stenosis is lower in the wrist than in mid-forearm AVFs (6), and others have suggested that the Qa threshold warranting imaging and intervention should depend on access site, a Qa limit of 400 ml/min being acceptable in the forearm as opposed to 600 ml/min in the upper arm AVFs (8).…”
Section: Introductionmentioning
confidence: 99%